Demonstration of Antigenic Polymorphism in Plasmodium vivax Malaria with a Panel of 30 Monoclonal Antibodies - Udagama, Preethi V.; David, Peter H.; Peiris, J. S. M.; Ariyaratne, Y. G.; Perera, K. L. R. L.; Mendis, Kamini N. (Infection and Immunity, 1987)
A panel of 30 monoclonal antibodies was established against asexual erythrocytic stages of Plasmodium vivax and used to investigate the antigenic composition of the parasite. At least 38 different antigenic polypeptides of P. vivax were characterized by the Western blot technique. The possible location of these antigens, as well as their stage and species specificity, was determined on the basis of the staining patterns produced by these antibodies on air-dried parasites in the indirect immunofluorescence test. Immunofluorescence performed with 30 different monoclonal antibodies on 50 different isolates of P. vivax obtained from patients showed that a high level of antigenic polymorphism prevailed in P. vivax. Only six monoclonal antibodies reacted with epitopes that were represented in more than 80% of parasite isolates, and therefore, appeared to be relatively conserved among different isolates. The other 24 monoclonal antibodies reacted with only 20 to 70% of parasite isolates.
Keywords: Antigenic polymorphism; monoclonal antibodies; Plasmodium vivax; malaria